Pengaruh CAR, NPF dan FDR Terhadap Pembiayaan Murabahah pada Bank Umum Syariah di Indonesia (Studi Kasus pada Bank Mandiri Syariah, Bank BNI Syariah dan Bank BRI Syariah Triwulan I-IV Tahun 2015-2019) - Nunuk Nafidzatun Nafiah; Mifta Hulaikhah; Ahmat Arif Syaifudin (JES (Jurnal Ekonomi Syariah), 2020)
The study aims to analyze the effect of CAR, NPF, FDR to mura>bah}ah financing on Islamic commercial banks simultaneously and partially. The dependent variable in this study is mura>bah}ah financing. The independent variables are CAR, NPF, FDR. The research of mura>bah}ah financing using a quantitative approach. The research population includes all registered Islamic banking in the Bank Indonesia period 2015-2019. The sample was determined by purposive sampling technique. The data used in this study are quarterly financial statement data three Islamic banks in Indonesia period 2015-2019. The method of analyzing data used multiple linear regression. The results of this study indicate that the partially capital adequacy ratio (CAR) variable significantly negative effect on mura>bah}ah financing with value sig. 0,0000 < 0,05. Non performing financing (NPF) variable significant negative effect on mura>bah}ah financing with value sig. 0,003 < 0,05. Financing deposit ratio (FDR) variable significant negative effect on mura>bah}ah financing with value sig. 0,0000 < 0,05. The results of this study indicate that capital adequacy ratio (CAR), non performing financing (NPF), and financing deposit ratio (FDR) variable effect simultaneously to  mura>bah}ah financing variable with value sig. 0,0000 < 0,05. Keywords: capital adequacy ratio; non performing financing; financing deposit ratio; mura>bah}ah financing